2019
DOI: 10.3390/mi10070465
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Surface Plasmon Resonance (SPR) in MoS2- and WS2-Protected Titanium Side-Polished Optical Fiber as a Humidity Sensor

Abstract: In this paper, we report the effects of a side-polished fiber (SPF) coated with titanium (Ti) films in different thicknesses, namely 5 nm, 13 nm, and 36 nm, protected by a thin layer of transition metal dichalcogenides (TMDCs) such as molybdenum disulfide (MoS2) and tungsten disulfide (WS2), which provide ultra-sensitive sensor-based surface plasmon resonance (SPR) covering from the visible to mid-infrared region. The SPF deposited with Ti exhibits strong evanescent field interaction with the MoS2 and WS2, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The fifth layer of TMDCs with the refractive index and thickness of monolayer at λ = 632.8 nm is shown in Table 1 [47,48]. In the sixth layer, the refractive index of graphene at visible range is obtained by the relation [49]:…”
Section: Theoretical Model and Methodsmentioning
confidence: 99%
“…The fifth layer of TMDCs with the refractive index and thickness of monolayer at λ = 632.8 nm is shown in Table 1 [47,48]. In the sixth layer, the refractive index of graphene at visible range is obtained by the relation [49]:…”
Section: Theoretical Model and Methodsmentioning
confidence: 99%
“…The sensitivity is 1.11 pm/%RH between 20%RH and 50%RH, and the dynamic range is 20%RH–50%RH. Rozalina Zakaria et al [ 164 ] demonstrated SPR in a titanium-coated side-polished optical fiber that is protected by a layer of 2D molybdenum disulfide (MoS 2 ) or tungsten disulfide (WS 2 ). Only the Ti/MoS 2 showed a response when changing the RH from 58% to 88%.…”
Section: Literature and The State-of-the-artmentioning
confidence: 99%
“…The typical response time was less 0.85 s. This is fast enough to monitor the humidity change during human breathing. Zakaria and co-workers utilized the MoS 2 thin film as the protecting layer for a titanium film, and coated the two films on a side-polished fiber. The SPR sensor is characterized by high sensitivity to RH in the range of 58–88% RH.…”
Section: Sensors For Humidity and Water Fractionmentioning
confidence: 99%